Challenges and perspectives of the indicators in the brazilian 2030 Agenda - Francisco, Daniel Neto; Villela, Lamounier Erthal (Revista Aval, 2022)
The present work seeks to bring to the debate an analysis on the construction of the 2030 Agenda and to analyze the challenges and perspectives in the establishment of a framework of indicators in the Brazilian subnational contexts. To this end, we seek to materialize the goals of the Sustainable Development Goals (SDGs) from national reports and documents, such as the Luz Report (2020), which present the scenario for monitoring the SDGs and their goals. The results show the fragility in the configuration of a systematization of local initiatives and contexts, as well as the dialogue between local spheres.